The extent of the commitment of Islamic banks in the Kurdistan Region of Iraq to the internal Sharia audit controls and their impact on enhancing the auditors’ confidence in accounting information: An exploratory study of the opinions of a sample of auditors and auditors in the Islamic Banking Control Department of the Central Bank, Erbil branch - Malik Mohammed Tawfeeq Fadhil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Islamic banks and the audit and oversight of their financial operations are considered a very important topic, especially in today’s day, due to the large number of financial operations that violate the Shariah of Islam in this field. For this purpose, this study focused on showing the extent of commitment of Islamic banks in the Kurdistan Region of Iraq to the internal Sharia audit controls and their impact on enhancing the confidence of auditors in accounting information. The questionnaire was used to obtain study data and analyze it using the statistical program (SPSS), and to achieve the research objectives The (One-Sample t-test), arithmetic mean, standard deviation, coefficient of variation and alpha-Cro-Nbach coefficient were applied. The results of the study showed, through statistical analyzes of the axes of the questionnaire, that Islamic banks in the Kurdistan Region of Iraq / Erbil adhere to the internal Sharia audit controls established by the Supervisory Board The legality of the Islamic Banks Control Department in the Central Bank, and the study also concluded that the commitment of Islamic banks to the internal Sharia audit controls have a positive and effective impact on enhancing the confidence of auditors in accounting information.